A systematic review of existing observational tools to measure the food and physical activity environment in schools. (November 2020) - Lane, Hannah G.; Calvert, Hannah G.; Deitch, Rachel; Harris, Ryan; Babatunde, Oyinlola T.; Turner, Lindsey; Hager, Erin R.; Jilcott Pitts, Stephanie
Abstract: Objective measures of schools' wellness-promoting environments are commonly used in obesity prevention studies; however, the extent to which findings from these measures translate to policy and practice is unknown. This systematic review describes the comprehensiveness and usability (practicality, quality, and applicability) of existing objective measures to assess schools' food and physical activity environments. A structured keyword search and standard protocol in electronic databases yielded 30 publications reporting on 23 measures that were deemed eligible to include in this review. Findings provide details to guide researchers and practitioners in selecting the best tool for use in policy and program evaluations. Highlights: Audit tools for school food and activity environments should be useful for both research and improving policy and practice. This systematic review describes comprehensiveness and usability of 23 existing audit tools that measure these environments. For comprehensiveness, many capture cafeteria and outdoor play areas, while few capture other relevant areas (classrooms). For usability, studies underreport key indicators (practicality, quality, applicability), limiting usability beyond research. To improve policy/practice relevance of audit data, researchers and stakeholders should collaborate to prioritize usability.